2020
DOI: 10.1002/jmor.21251
|View full text |Cite
|
Sign up to set email alerts
|

Appendage regeneration in anamniotes utilizes genes active during larval‐metamorphic stages that have been lost or altered in amniotes: The case for studying lizard tail regeneration

Abstract: This review elaborates the idea that organ regeneration derives from specific evolutionary histories of vertebrates. Regenerative ability depends on genomic regulation of genes specific to the life-cycles that have differentially evolved in anamniotes and amniotes. In aquatic environments, where fish and amphibians live, one or multiple metamorphic transitions occur before the adult stage is reached. Each transition involves the destruction and remodeling of larval organs that are replaced with adult organs. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 131 publications
0
37
0
Order By: Relevance
“…While not having the regenerative capabilities of amphibians, reptiles nonetheless have considerable capacities for regeneration. While the regeneration of gross structures (e.g., limbs, tail) have been studied in reptiles [136], there appears to have been little focus specifically on neural regeneration, and especially of the NVU. In the lizard Gallotia galloti, studies of cellular performance following transection of the optic nerve indicate rapid restoration of key components of the neurovascular barrier within a few weeks [137].…”
Section: Factors Altering Reptilian Blood-brain Barrier Functionmentioning
confidence: 99%
“…While not having the regenerative capabilities of amphibians, reptiles nonetheless have considerable capacities for regeneration. While the regeneration of gross structures (e.g., limbs, tail) have been studied in reptiles [136], there appears to have been little focus specifically on neural regeneration, and especially of the NVU. In the lizard Gallotia galloti, studies of cellular performance following transection of the optic nerve indicate rapid restoration of key components of the neurovascular barrier within a few weeks [137].…”
Section: Factors Altering Reptilian Blood-brain Barrier Functionmentioning
confidence: 99%
“…These vertebrates, typically certain anamniotes, whose life is adapted to the aquatic environment, in particular amphibians with the capacity to regenerate extensively entire organs [ 112 , 23 , 79 ]. One school of thought posits that amphibian regeneration is linked to three things: (1) the transition from water to land via the larval stage and thus having elaborate genetic programs for metamorphosis in which the immune system recognize antigens of larval tissues as not-self and destructs the transitory tadpole organs that are replaced by new organs [ 5 ], (2) regeneration is facilitated by a high level of hydration and hyaluronate content to allow the formation of the blastema [ 4 ] and (3) an underdeveloped or suppressed immune system to allow embryoid tissue to develop and new structures be formed. Thus, the low activity or underdeveloped nature of the immune system, in particular the adaptive arm of it, in anamniotes facilitates organ regeneration since the blastema formed after an injury is tolerated long enough to allow regeneration [ 44 46 , 62 ].…”
Section: The Evolutionary and Developmental Relationship Between Immunity And Regenerationmentioning
confidence: 99%
“…A subsequent study on the expression of the main genes in regeneration compared to scarring tails confirmed that wnt2b, wnt6, c-myc, egfl6, and arhgap28 are among the main genes stimulating tail regeneration [ 71 ]. The study has continued until today, with the immunodetection of numerous coded proteins in both the tail and limbs (summarized in [ 32 , 72 , 73 , 74 , 75 ]). As a result of the above studies on lizards in comparison to fish and amphibian regeneration genes, I elaborated a new evolutionary explanation for the lack of organ regeneration in terrestrial vertebrates [ 32 , 74 ].…”
Section: The Lizard Model: Brief Historical Notesmentioning
confidence: 99%
“…The study has continued until today, with the immunodetection of numerous coded proteins in both the tail and limbs (summarized in [ 32 , 72 , 73 , 74 , 75 ]). As a result of the above studies on lizards in comparison to fish and amphibian regeneration genes, I elaborated a new evolutionary explanation for the lack of organ regeneration in terrestrial vertebrates [ 32 , 74 ].…”
Section: The Lizard Model: Brief Historical Notesmentioning
confidence: 99%
See 1 more Smart Citation